Belostomatidae Leach, 1815 (Insecta: Hemiptera: Heteroptera: Nepomorpha) of northeastern Brazil - Franco, Cleilton Lima; Stefanello, Fabiano; Azevêdo, Carlos Augusto Silva de; Moreira, Felipe Ferraz Figueiredo (European Journal of Taxonomy, 2024)
Belostomatidae Leach, 1815 (Insecta: Hemiptera: Heteroptera: Nepomorpha), also known as giant water bugs, is a family with 11 genera and about 160 described species, most of which are recorded from the Neotropical region. Knowledge about these bugs in northeastern Brazil is relatively poor, with 16 previously recorded species. Here, we present new records for five additional species based on material from the states of Ceará, Maranhão, and Piauí deposited in the Coleção Zoológica do Maranhão, Caxias, Brazil. This increases to 21 the number of species recorded from the region. In addition, we provide photographs, distribution maps, and a key to the fauna of Belostomatidae from northeastern Brazil.